Bottom-coupled parallel-cascaded ring resonators passband filter / Siti Naslina Darame - Darame, Siti Naslina (2010)
In this paper, a bottom - coupled parallel - cascaded ring resonators passband filter is designed at 3GHz center frequency. Based on ring topology, the filter is design by cascading of two ring resonators with two coupled lines are connected in parallel at the input and output port. The purpose of this new topology design is to know the response of the filter. The number of poles will be increased from 2nd order to 4th order because of having the cascading ring resonators and two of coupled lines. The filter is realized using FR4 substrate with a relative dielectric constant of 5.4, thickness of 1.6 mm and loss tangent of 0.02.